2000
DOI: 10.1017/s1355617700677032
|View full text |Cite
|
Sign up to set email alerts
|

Category Fluency Test: Normative data for English- and Spanish-speaking elderly

Abstract: Category fluency tasks are an important component of neuropsychological assessment, especially when evaluating for dementia syndromes. The growth in the number of Spanish-speaking elderly in the United States has increased the need for appropriate neuropsychological measures and normative data for this population. This study provides norms for English and Spanish speakers, over the age of 50, on 3 frequently used measures of category fluency: animals, vegetables, and fruits. In addition, it examines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
6
11

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(119 citation statements)
references
References 42 publications
(73 reference statements)
8
94
6
11
Order By: Relevance
“…Male subjects generated slightly more items than females in terms of total scores and intervals 2, 3, 4, and in terms of number of clusters, with significance only in generation between 15 and 30 s. Similar findings were reported by Kempler et al (21), in whose study men performed better than women. However, other studies have presented better performance by women in verbal fluency (14,20,23,28). Nevertheless, we failed to find a gender effect, as did our previous survey (24).…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Male subjects generated slightly more items than females in terms of total scores and intervals 2, 3, 4, and in terms of number of clusters, with significance only in generation between 15 and 30 s. Similar findings were reported by Kempler et al (21), in whose study men performed better than women. However, other studies have presented better performance by women in verbal fluency (14,20,23,28). Nevertheless, we failed to find a gender effect, as did our previous survey (24).…”
Section: Discussioncontrasting
confidence: 78%
“…Many studies have revealed the influence of education on total scores (17)(18)(19)(20)(21)(22)(23). In a previous survey of a Brazilian sample based on educational level, we determined cut-off scores of 9 for illiterates and subjects aged <8 years, and of 13 for persons with more than 8 years of schooling (24).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, limited studies have produced verbal fluency test norms in Spanish-speakers in the United States (Lucas et al, 1998;Stricks et al, 1998;Acevedo et al, 2000). The current study was the first to generate verbal fluency test norms across 11 countries in Latin America with nearly 4,000 participants.…”
Section: Limitations and Future Directionsmentioning
confidence: 82%
“…Metanorms and individual norms studies have been completed for the phonological verbal fluency task using the cluster of letters F, A, and S, most commonly with English speaking adults in the United States and Canada (Acevedo et al, 2000;Gladsjo et al, 1999;Heaton, 2004;Loonstra, Tarlow, & Sellers, 2001;Mitrushina, 2005;Tombaugh, Kozak, & Rees, 1999). Additionally, norms have been established in the United States for phonological fluency using the letters C, F, and L (Ruff, Light, Parker, & Levin, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation